Mitigation of voltage imbalance in power distribution system using MPC‐controlled packed‐U‐cells converter. Issue 5 (23rd August 2019) - Ahmed, Ibrahim; Al‐Emadi, Nasser; Gastli, Adel; Ben‐Brahim, Lazhar
Abstract: Delivering high power quality in single‐phase distribution has witnessed more challenges especially with the increased penetration of single‐phase distributed generation (DG). This paper proposes a smart solid‐state‐based transformer, which aims to replace traditional ones, for single‐phase distribution laterals, and provide load balancing and protection to the three‐phase main feeders, that is based on connecting the single‐phase lateral to the three‐phase main feeder through a power electronics converter. This converter transfers balanced power from and to the three‐phase feeder while automatically regulating the lateral single‐phase voltage, hence, assuring high power quality without requiring any transformer on‐load tap changer. A 7‐level packed‐U‐cells (PUC) single‐phase inverter topology was used to deliver single‐phase regulated sinusoidal voltage to the AC loads, and at the same time, it is able to deliver DC power to DC loads. The simulation and hardware‐in‐the‐loop (HIL) results have shown that the proposed topology delivers high power quality for both AC and DC loads under different operating scenarios. Moreover, the converter can play the role of a solid‐state protection device coordinated with other up‐ and downstream protective devices. Finally, this system can be integrated within the smart grid allowing more flexibility for automation and efficient control of the grid. Abstract : This paper proposes a smart solid‐state‐based transformer, which aims to replace traditional ones, for single‐phase distribution laterals and provides load balancing and protection to the three‐phase main feeders. The proposed topology is based on connecting the single‐phase lateral to the three‐phase main feeder through a power electronics converter.